HR management in M&A. - Thom, Marcel G. (2008)
This thesis aims to provide a structured approach to handle M&A transactions from an HR point of view. By use of ‘HRM Cube in M&A”, issues like job losses, restructured responsibilities, derailed careers, diminished power, insecurity, changed relationship and other stressful experiences can be addressed.